STRATEGI GURU DALAM PEMBELAJARAN LITERASI DASAR BAGI SISWA KELAS IV TERHADAP PENINGKATAN MEMBACA ABJAD DI UPT SD NEGERI 169 SADAR - Widya Hastuti; Zul Andrivat (MURABBI, 2025)
Basic literacy skills are the main foundation in the learning process in elementary school. However, there are still high class students who do not know the letters of the alphabet. This study aims to describe teachers' strategies in learning basic literacy for grade IV students at UPT SD Negeri 169 Sadar who experience literacy delays. This study uses a descriptive qualitative approach. Data was collected through observation, interviews, and documentation, then analyzed by data reduction techniques, data presentation, and conclusion drawn. The results showed that teachers used three main strategies, namely: (1) phonics learning to introduce the relationship between letters and sounds, (2) the use of concrete media such as letter cards, pictures, and real objects, and (3) an individual and collaborative approach with parents. This strategy helps students recognize letters, read simple words, and increase learning motivation. This research emphasizes the importance of teacher innovation in adapting learning to the needs of students who experience delays in basic literacy.